Os (des)caminhos da representação da identidade em A majestade do Xingu, de Moacyr Scliar, e O olho de Hertzog, de João Paulo Borges Coelho - Rodrigues, Célia Aparecida Ribeiro (2022)
This research aims to compare the novels “A majestade do Xingu” (1997), by the Brazilian author Moacyr Scliar, and “O olho de Hertzog” (2010), by the Mozambican writer João Paulo Borges Coelho. Without losing sight of the literary and fictional character of the narrative, the aim is to problematize the representation of the identity processes of the main characters based on the articulation of theoretical concepts of Cultural Studies, especially according to Stuart Hall (2013; 2014a; 2014b). The debate occurs from the interweaving of the notions of identity, difference, and representation. For the sociologist, the questioning about identity only gains prominence for the individual when confronted with another way of being in the world. Thus, the status of identity and difference is examined since in their attempt to know themselves, the narrators, both foreigners, make their differentiation explicit by looking at the Other. The narratives under analysis are inserted in the macrosystem of Portuguese-speaking countries (ABDALA JÚNIOR, 1989) and reflect political and historical events in both Mozambique and Brazil. The results point to the fragmentation of the narrator-character identity that reverberate national identities, also complex and plural. By vocalizing about their (un)similarities, these narrators make themselves known and reveal the cultural complexity of the two countries, both of which come from the colonial experience that, in turn, echoes the difficulty of dialoguing with difference. In this way, beyond the reflection on artistic creation, the novels evoke the web of the past, shedding light on the knots of the present.